Numerical Simulation of Engineered Material Arrestor System (EMAS) - Amirhossein Akbarikermani; Farzin Kalantary (Numerical Methods in Civil Engineering)
With the increasing speed and weight of modern passenger aircraft, the need for longer runways has become more critical than ever. To address safety concerns, the Federal Aviation Administration (FAA) has mandated a 305-meter (1,000-foot) safety zone, known as the Runway Safety Area (RSA), at the end of runways at major airports. However, in many cases, this requirement cannot be met due to natural or man-made obstacles within the airport's boundaries. As a solution, the implementation of an Engineered Material Arrestor System (EMAS) has been proposed. EMAS is designed to significantly reduce the stopping distance of aircraft during overrun events, minimizing both passenger discomfort and the risk of structural damage to the aircraft. The objective of this paper is to investigate and simulate the performance of EMAS using finite element analysis software capable of handling large deformation problems. The Arbitrary Lagrangian-Eulerian (ALE) formulation is utilized to conduct large deformation analyses. In the simulations, three types of aircraft are modeled to enter a hypothetical EMAS bed at a speed of 70 knots (130 km/h). Additionally, three types of foam concrete with different densities are selected for the EMAS bed material. The results demonstrate that higher-density materials exhibit greater stiffness, resulting in shorter stopping distances for the aircraft. As expected, lower-density (softer) materials apply less force and deceleration to the aircraft. Furthermore, the findings indicate that lighter aircraft experience higher deceleration forces than heavier aircraft, regardless of the bed material. However, heavier aircraft generate higher overall impact forces during the overrun.